Extraction of fusion relevant ion species from discharge of focused anode layer thruster - Girka, O.; Bizyukov, O.; Kolyada, Yu.; Sereda, K.; Bizyukov, I. (Вопросы атомной науки и техники, 2015)
The modification of anode layer thruster, which utilizes the focusing with reversed magnetic field (FALCON ion source), has been investigated for operation with H, He and Ar working gases. Current efficiency was measured to be in the range of 30…40% for H and Ar ion beam, while for He gas it varies from 10 to 20%.